2010
DOI: 10.3390/s100908332
|View full text |Cite
|
Sign up to set email alerts
|

Sturdy Positioning with High Sensitivity GPS Sensors Under Adverse Conditions

Abstract: High sensitivity GPS receivers have extended the use of GNSS navigation to environments which were previously deemed unsuitable for satellite signal reception. Under adverse conditions the signals become attenuated and reflected. High sensitivity receivers achieve signal reception by using a large number of correlators and an extended integration time. Processing the observation data in dynamic and rapidly changing conditions requires a careful and consistent treatment. Code-based autonomous solutions can caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…The degradation of GNSS signals in forests (e.g., [55,56]) makes it often necessary to use total station measurements. In cases where the survey cannot be conducted from a single occupation point, this means complications and increased time consumption.…”
Section: Discussionmentioning
confidence: 99%
“…The degradation of GNSS signals in forests (e.g., [55,56]) makes it often necessary to use total station measurements. In cases where the survey cannot be conducted from a single occupation point, this means complications and increased time consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Usually only the code and phase observations are used for determining position. Kozmus Trajkovski et al (2010) showed that Doppler measurements may significantly improve position determination, especially in adverse conditions in which phase observations are useless.…”
Section: Introductionmentioning
confidence: 99%
“…The calculated correction message is transferred to the rover, to enable highly accurate real-time positioning [4]. Multiple GPS reference stations are utilized, because using a single reference station reduces accuracy if the distance between the rover and the reference station exceeds 10 km [5,6]. The NRTK correction message may be calculated using the data from multiple GPS reference stations placed at intervals of 50–70 km across a wide area, and the results may then be transferred in NTRIP format.…”
Section: Introductionmentioning
confidence: 99%